The Rise of Silver Man at the Intersection of Purwokerto City Traffic Lights - Muhammad Axel Radindasyah (UM Purwokerto Press, 2023)
One of the social symptoms in society is the phenomenon of the emergence of the silver man at the red light intersection of Purwokerto City. Silver people are not beggars but street artists, they peddle themselves with sculpture knowledge and hope to get rewards from art lovers, especially sculpture for their own survival with their families. The purpose of this research is to analyze the existence of the silver man, when it emerged and what motivated someone to become a silver man. The solidarity of the silver human community in maintaining the life and economy of the family makes this research a problem formulation. Using descriptive qualitative research methods, such as observation, interviews and document studies, researchers collect data from the field, analyze, present and draw conclusions. From all the data collected, researchers concluded that the emergence of silver people is based on the demands of life or survival where work opportunities are very narrow and limited, limited education and various types of poverty. They are considered beggars and become a social problem in society because they ask for rewards from road users, they are also the target of arrest from the pamong praja police because they are considered disturbing order and security so they are always chased and sent to the city or district social service.